2018
DOI: 10.3390/ijerph15020284
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Investigation of Selected Taste and Odor Compounds by a UV/Chlorine Advanced Oxidation Process

Abstract: Taste- and odor-causing (T&O) compounds are a major concern in drinking water treatment plants due to their negative impacts on the safety and palatability of water supply. This study explored the degradation kinetics and radical chemistry of four often-detected T&O compounds, geosmin (GSM), 2-methylisoborneol (MIB), benzothiazole (BT), and 2-isobutyl-3-methoxypyrazine (IBMP), in the ultraviolet/chlorine (UV/chlorine) advanced oxidation process. All experiments were carried out in a 700 mL photoreactor and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…For the case of the UV/Cl 2 process, it is known that there are formation of reactive chlorine species (i.e., Cl•, Cl 2 − •, and ClO•), but it was reported that OH• is a primarily radical species to the degradation of taste-and-odor compounds as compared to reactive chlorine species which are formed in the UV/Cl 2 process [36]. Treatment in the presence of algae species using oxidation processes has drawbacks such as undesirable toxins and taste and odor compounds [37,38]; therefore, the AOPs were applied after the coagulation process with the optimum PMC dose, i.e., 20 mg/L.…”
Section: Uv/h 2 O 2 and Uv/cl 2 For Tando Removal Lab-scalementioning
confidence: 99%
“…For the case of the UV/Cl 2 process, it is known that there are formation of reactive chlorine species (i.e., Cl•, Cl 2 − •, and ClO•), but it was reported that OH• is a primarily radical species to the degradation of taste-and-odor compounds as compared to reactive chlorine species which are formed in the UV/Cl 2 process [36]. Treatment in the presence of algae species using oxidation processes has drawbacks such as undesirable toxins and taste and odor compounds [37,38]; therefore, the AOPs were applied after the coagulation process with the optimum PMC dose, i.e., 20 mg/L.…”
Section: Uv/h 2 O 2 and Uv/cl 2 For Tando Removal Lab-scalementioning
confidence: 99%
“…However, some researches show that contributions of both HO˙ and RCS increase with a decrease in pH [31,37,40,79]. This discrepancy can be explained by the radical scavenger effect of ClO − [5,16,40,77,79]. Since reaction rate constants of ClO − with HO˙, Cl˙, and Cl 2˙− are higher than those of HOCl (Table 1), the radical scavenging effect of free chlorine is stronger in basic pH than in acidic pH.…”
Section: Effect Of Phmentioning
confidence: 98%
“…Thus, it is expected that the relative contribution of HO˙ decreases at acidic pH, if pollutants are reactive with RCS. However, some researches show that contributions of both HO˙ and RCS increase with a decrease in pH [31,37,40,79]. This discrepancy can be explained by the radical scavenger effect of ClO − [5,16,40,77,79].…”
Section: Effect Of Phmentioning
confidence: 98%
See 1 more Smart Citation
“…The potential risks resulting from the occurrence of BP and HBP must not be overlooked.Advanced oxidation processes (AOPs) are a series of processes that can generate hydroxyl radicals to efficiently degrade organic pollutants in contaminated water [4,14,15]. The UV/H 2 O 2 system is a type of AOP, in which hydrogen peroxide (H 2 O 2 ) is added in the presence of UV light to generate hydroxyl radicals [16][17][18]. It is found that the UV/H 2 O 2 process can remove a large range of organic pollutants, including cyanobacterial toxins [19], diclofenac [20], amoxicillin [21], and other emerging contaminants [22][23][24].Benzophenone-type UV filters are usually the hardly biodegradable substances [25].…”
mentioning
confidence: 99%